Global labor migration : new directions - Boris, Eileen, 1948-; Gottfried, Heidi, 1955-; Greene, Julie; Tham, Joo-Cheong (Studies of world migrations., 2023)
"Around the world, hundreds of millions of labor migrants endure exploitation, lack of basic rights, and institutionalized discrimination and marginalization. What factors created a system that forces this huge and growing mass of human beings to toil as an institutional and judicial lower caste? In what ways did labor migrants shape their living and working conditions in the past, and what opportunities exist for them today? Global Labor Migration presents new multidisciplinary, transregional perspectives on issues surrounding global labor migration. The essays go beyond disciplinary boundaries, with sociologists, ethnographers, legal scholars, and historians contributing research that extends comparison among and within world regions. Looking at migrant workers from the late nineteenth century to the present day, the contributors illustrate the need for broader perspectives that study labor migration over longer timeframes and from wider geographic areas. The result is a unique, much-needed collection that delves into one of the world's most pressing issues, generates scholarly dialogue, and proposes cutting-edge research agendas and methods"--